Soil functions – Today’s situation and further development under climate change - Madena, Kirsten; Bormann, Helge; Giani, Luise (ERDKUNDE, 2012)
Climate change will have effects on many ecosystems, including the top layer of the earth: the soils. Climate-induced changes in soil properties can lead to changes in soil functions and their importance for soil protection. These possible changes have been evaluated within the German part of the EU Interreg IVb project “Climate Proof Areas” in two pilot regions in the Wesermarsch (Germany). The evaluation of eight different soil sub-functions was carried out using the evaluation method TUSEC-B based on soil information gained from soil maps for present (Status Quo) and climate-adapted soil properties. Four different climate scenarios for 2050 were considered. The evaluation results of the individual soil functions have been summarized to an overall evaluation result using the maximum principle. The evaluation results for the Status Quo show that large areas of the pilot regions are important for soil protection regarding both the individual soil function evaluation and the summarized evaluation. The adaptation of climate-influenced evaluation parameters results in an increase of the importance of protection of the soils for some sub-regions and in a decrease for others, depending on the scenario. The differences in the extent and direction of changing evaluation results mainly depend on changes in soil organic matter content and groundwater level. They are different for the individual soil functions and regarding the overall evaluation result, but show the influence of climate change on soil functions. On the basis of these results, it is recommended to consider climate-induced changes in soil functions within spatial planning processes such as area-wide coastal protection or water management measures (e.g., dike or reservoir construction), to avoid the loss of soils with valuable functions that are worth protecting.